Ajaran Agama Hindu dalam Cerita Batur Taskara - Ida Bagus Putu Eka Suadnyana (Sanjiwani: Jurnal Filsafat, 2020)
Hindu teachings is poured in the legacy of Hindu literary works in the form of stories or Hindu mythology, such as stories of Babad, Tantri, the epic Mahabharata and the Ramayana. The literary works that are inherited certainly have features in them, one of which is the Tantri story. From the various Tantri stories that exist, in this study raised one of the Tantri stories entitled Batur Taskara. In essence, this story tells about the occurrence of the law of cause and effect from the actions of the previous Batur Taskara. This scientific work in the form of descriptive qualitative design. This scientific work is purely studying texts. Data were collected using document study techniques and interview techniques. After the data is collected, the data is analyzed through three stages namely data reduction, data presentation, and drawing conclusions. Based on this analysis, conclusions are obtained as a result, as follows: (1) The structure of the Batur Taskara story includes, synopsis, themes, plot, characters, background and message of the story. (2) The teachings of Hinduism contained in the Batur Taskara story are the teachings of Yoga, Panca Satya, Sad Ripu and Karmaphala.